Gothic Backgrounds of 16 th Century tales: The Gost (Castilla. Estudios de Literatura, 2019)
The spectre, the shadow, the spirit, the larva, the revenant, or the phantom has formed part of humanity’s collective memory since ancient times. Dreading the return of the dead has forever been an anthropological and ancestral fear. Thus, we find the presence of ghosts in many of the stories and tales of the sixteenth century. We will analyse the Spanish works of three authors - three ghost stories set in houses, caves, or large mansions. We will describe the plots, environments, motifs and sensations that contributed to creating an imaginary that would later give rise to Gothic literature. In this way, we will explore the Gothicism of 16th century ghost literature.
Keywords: phantom; reveant; literatur of the sixteen century; gothicism; terror